1995
DOI: 10.1093/infdis/171.4.1022
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Sexual and Mother-to-Child Transmission of Human T Lymphotropic Virus Type II among Guaymi Indians, Panama

Abstract: Guaymi Indians, a non-intravenous drug-using population in which human T cell lymphotropic virus type II (HTLV-II) is endemic, were studied in Changuinola, Panama, to identify the prevalence and modes of transmission of HTLV-II. A population-based survey showed that 352 (9.5%) of the 3686 participants were seropositive for HTLV-II. Infection rates were the same for male and female subjects and increased significantly with age, beginning in young adulthood. HTLV-II infection status was highly concordant among s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
4

Year Published

1997
1997
2011
2011

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 9 publications
0
16
0
4
Order By: Relevance
“…The high seroprevalences among indigenous tribes in the Amazon region of Brazil are some of the most compelling evidence of sexual transmission, since injection-drug use is virtually absent in these isolated communities and transmission is presumed to occur primarily through sexual contact and breast-feeding. Sexual transmission is further supported by studies showing a gradual increase in HTLV-II seropositivity with age, perhaps as a result of exposure to more sex partners throughout life [19,30]. Moreover, a survey of Kayapo Indian communities found similar seroprevalences among men and women (31.4% vs. 34.2%; ), P !…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The high seroprevalences among indigenous tribes in the Amazon region of Brazil are some of the most compelling evidence of sexual transmission, since injection-drug use is virtually absent in these isolated communities and transmission is presumed to occur primarily through sexual contact and breast-feeding. Sexual transmission is further supported by studies showing a gradual increase in HTLV-II seropositivity with age, perhaps as a result of exposure to more sex partners throughout life [19,30]. Moreover, a survey of Kayapo Indian communities found similar seroprevalences among men and women (31.4% vs. 34.2%; ), P !…”
Section: Discussionmentioning
confidence: 80%
“…Several cross-sectional studies have identified sexual contact as an important risk factor for HTLV-II infection, particularly among indigenous populations in whom injection-drug use is rare, thus pointing strongly to evidence of sexual transmission [19][20][21][22]. Because of a lack of long-term follow-up of these non-IDU populations, an incidence rate (IR) of sexual transmission of HTLV-II remains unknown.…”
mentioning
confidence: 99%
“…HTLV-II seroprevalence is higher in women and increases steadily with age among Panamanian Guaymi [31] and Argentinian Gran Chaco [32] Indians. The Indian pattern, reminiscent of that for HTLV-I endemic populations, has been attributed to ongoing sexual transmission, which is more efficient from men to women than from women to men.…”
Section: Discussionmentioning
confidence: 91%
“…One group exhibits neurologic deficits resembling those of HTLV-I-associated myelopathy/tropical spastic paraparesis (HAM/TSP) [8][9][10], while the other manifests symptoms of tropical ataxic neuropathy (TAN) [11][12][13][14]. High rates of HTLV-II infection have been documented for the same five behavior patterns attributed to transmission of the HTLV-I virus [15]: sexual intercourse [16][17][18], breast feeding [19][20][21][22][23], blood transfusion [24][25][26][27][28][29], intravenous drug use and drug needle sharing [30][31][32][33][34][35][36][37][38][39][40], although intravenous drug users remain the highest risk group for HTLV-II in the USA [19,41]. In addition, HTLV-II infection has been shown to be endemic in certain New World Amerindian populations including the Seminole Indians in Florida [42,43], the Navajo and Pueblo tribal groups in New Mexico [44], the Cayapo and Kraho tribes in Brazil [17,[45][46][47], the Guaymi Indians in Panama [48]…”
Section: Introductionmentioning
confidence: 99%